Electron losses from the radiation belts caused by EMIC waves. Issue 11 (5th November 2014) - Kersten, Tobias; Horne, Richard B.; Glauert, Sarah A.; Meredith, Nigel P.; Fraser, Brian J.; Grew, Russell S.
Abstract Electromagnetic Ion Cyclotron (EMIC) waves cause electron loss in the radiation belts by resonating with high‐energy electrons at energies greater than about 500 keV. However, their effectiveness has not been fully quantified. Here we determine the effectiveness of EMIC waves by using wave data from the fluxgate magnetometer on CRRES to calculate bounce‐averaged pitch angle and energy diffusion rates for L*=3.5–7 for five levels of Kp between 12 and 18 MLT. To determine the electron loss, EMIC diffusion rates were included in the British Antarctic Survey Radiation Belt Model together with whistler mode chorus, plasmaspheric hiss, and radial diffusion. By simulating a 100 day period in 1990, we show that EMIC waves caused a significant reduction in the electron flux for energies greater than 2 MeV but only for pitch angles lower than about 60°. The simulations show that the distribution of electrons left behind in space looks like a pancake distribution. Since EMIC waves cannot remove electrons at all pitch angles even at 30 MeV, our results suggest that EMIC waves are unlikely to set an upper limit on the energy of the flux of radiation belt electrons.